PENGARUH CASH RATIO DAN DEBT RATIO TERHADAP RETURN ON ASSETS PADA PERUSAHAAN PERTAMBANGAN MINYAK DAN GAS YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2015-2019 - Kusminaini Armin (Universitas Tridinanti, 2020)
ABSTRACKThis study aims to determine how much effect of cash ratio and debt ratio as independent variables simultaneously and partially on return on assets as dependent variable using data consisting of 6 companies listed on IDX. The population of this study is a public company listed in IDX with oil and gas mining companies as the sample. This research uses purposive sampling method. Analysis of the data used in this study is a classic assumption test and for hypothesis testing using multiple linear regression analysis.The result of this study indicate that simultaneously cash ratio dan debt ratio have a significant effect on return on assets with a value of Fcount 3,361 while Ftable is 3,35 or in other words Fcount > Ftable with a significant value of 0,005 < 0,05 from the output value of SPSS. Partially there is no effect of cash ratio (X1) on return on assets. With a regression coefficient value -0,036 and tcount -2,242 < ttable 1,073 with a significant value of 0,078 > 0,05. While debt ratio (X2) has a significant effect on return on assets. With a regression coefficient value 0,072 and tcount 1,835 > ttable 1,073 with a significant value 0,033 < 0,05 Keywords : Cash ratio, Debt ratio dan Return on Assets